The gendered experience with respect to health-seeking behaviour in an urban slum of Kolkata, India - Moumita Das; Federica Angeli; Anja J. S. M. Krumeich; Onno C. P. van Schayck (BMC, 2018)
Abstract Background Empirical evidence shows that the relationship between health-seeking behaviour and diverse gender elements, such as gendered social status, social control, ideology, gender process, marital status and procreative status, changes across settings. Given the high relevance of social settings, this paper intends to explore how gender elements interact with health-seeking practices among men and women residing in an Indian urban slum, in consideration of the unique socio-cultural context that characterises India's slums. Methods The study was conducted in Sahid Smriti Colony, a peri-urban slum of Kolkata, India. The referral technique was used for selecting participants, as people in the study area were not very comfortable in discussing their health issues and health-seeking behaviours. The final sample included 66 participants, 34 men and 32 women. Data was collected through individual face-to-face in-depth interviews with a semi-structured questionnaire. Results The data analysis shows six categories of reasons underlying women's preferences for informal healers, which are presented in the form of the following themes: cultural competency of care, easy communication, gender-induced affordability, avoidance of social stigma and labelling, living with the burden of cultural expectations and geographical and cognitive distance of formal health care. In case of men ease of access, quality of treatment and expected outcome of therapies are the three themes that emerged as the reasons behind their preferences for formal care. Conclusion Our results suggest that both men and women utilise formal and informal care, but with different motives and expectations, leading to contrasting health-seeking outcomes. These gender-induced contrasts relate to a preference for socio-cultural (women) versus technological (men) therapies and long (women) versus fast (men) treatment, and are linked to their different societal and familial roles. The role of women in following and maintaining socio-cultural norms leads them to focus on care that involves long discussions mixed with socio-cultural traits that help avoid economic and social sanctions, while the role of men as bread earners requires them to look for care that ensures a fast and complete recovery so as to avoid financial pressures.